BCG vaccine effectiveness in the prevention of pulmonary tuberculosis in North Leyte - Cajano, Teresita M.
Objectives: The general objective of the study was to assess the effectiveness of BCG vaccination in the prevention of PTB. Specifically, the study wanted to determine the association between BCG vaccination received at infancy, at school entrance and at infancy with a booster dose at school entrance and Pulmonary Tuberculosis (PTB); and to estimate the preented fractions of the different categories of BCG vaccination. Methodology: This was a facility-based case-conrol study done in Tacloban City and the three health districts nearest to it in North Leyte. There were 127 cases and 251 controls included in the study. The cases were new PTB patients diagnosed to have the disease based on a positive sputum examination and/or positive chest-X-ray and a decision of a physician to treat with a full course of anti-TB therapy. The presence or absence of a BCG scar was used as an indicator for the subject's BCG vaccination status. Data was collected through records-review, face-toface interview, and direct observation using an Information Checklist and an interview schedule. Univariate, stratified and multivariate analysis were performed. Results: Showed that BCG vaccination had a protective effect against PTB regardless of the age at which it was received. Of the three categories of BCG vaccination, the strongest OR (ORa=0.24; 0.12, 0.48) and the least Prevented fraction (PF=.076) was among those who received the vaccine at infancy. The weakest OR (ORa=.037; 0.21, 0.66) and the smallest Prevented Fraction (PF=.063) was among those who received the vaccine at school entrance. Conclusions: BCG vaccination appears to have a protective effect against PTB. This protective effect is strongest when the vaccine is given at infancy and weakest when it is given at school entrance. Recommendations: It is recommended that a regional or nationalstudy be done to validate the findings in the present study. If similar results are found, this information will be useful to policy makers in the health sector and the Local Government Units (LGUs). Appropriate policies can be formulated such as: making BCG vaccination a must for every infant in the country, and allocating funds for the above purpose and for future research in this area.
Thesis (MS Epidemiology, Public Health)-- University of the Philippines Manila
Keywords: Tuberculosis; BCG vaccination .